A non-canonical promoter element drives spurious transcription of horizontally acquired bacterial genes - Warman, Emily A (Nucleic Acids Res, 2020)
RNA polymerases initiate transcription at DNA sequences called promoters. In bacteria, the best conserved promoter feature is the AT-rich -10 element; a sequence essential for DNA unwinding. Further elements, and gene regulatory proteins, are needed to recruit RNA polymerase to the -10 sequence. Hence, -10 elements cannot function in isolation. Many horizontally acquired genes also have a high AT-content. Consequently, sequences that resemble the -10 element occur frequently. As a result, foreign genes are predisposed to spurious transcription. However, it is not clear how RNA polymerase initially recognizes such sequences. Here, we identify a non-canonical promoter element that plays a key role. The sequence, itself a short AT-tract, resides 5 base pairs upstream of otherwise cryptic -10 elements. The AT-tract alters DNA conformation and enhances contacts between the DNA backbone and RNA polymerase.